Study guides

☆☆

Q: If 2x plus 3x equals 5x 2k plus 3k equals?

Write your answer...

Submit

Still have questions?

Related questions

k=4

==> 3k+14=k ==>3k-k=-14 ==>2k=-14 ==>k=-7 ans...

2k - 3k - m + 2m = -k + m

3k-1=k+2 2k=3 k=3/2=1.5

It can be simplified to: 9k

When factored it is: (3k+5)(k-1)

-4. -3k+10=k+2.... First we have to move the K to one side -3k+10=k+2 __________ This will reduce -3k to -2k and k+2 to just 2 K -2k+10=2 Now we have to subtract 10 to both sides as to get k alone. -2k+10=2 ________ Now we should have -2k on one side and 2-10 on the other. -10 -2k=2-10....... 2-10= 8. We have to get -2k into just K on itself so we divide by 2. -2k=-8 ______ Your answer is 4. You have to do one side what you do the other. 2

The above expression can be simplified to:14n-2k

It simplifies to 7k = 49 which gives k = 7.

3k + 3 = 8 3k = 8 -3 3k = 5 k = 5/3

3k+16 = 5k subtract 3k from both sides 16 = 2k divide both sides by 2 8 = k

Take 3k from both sides to get k-3 equals 4, so k is 7

2k = 5k-30 Subtract 5k from both sides: -3k = -30 Divide both sides by -3 to find the value of k remembering that a minus divided into a minus becomes a plus: k = 10

-k + 3k = 2k

1k/2k, 2k/4k, 3k/6k and so on.

9 - 2k - 3 = k Add 2k to both sides: 9 - 3 = k + 2k Combine like terms: 6 = 3k Divide both sides by 3: 2 = k

The non zero multiples of a number k are all numbers which can be written as n*k where n is not 0. So ..., -3k, -2k, -1k, 1k, 2k, 3k, ...

-47 + 6k = 3k - 2Add 47 to each side:6k = 3k +45Subtract 3k from each side:3k = 45Divide each side by 3:k = 15

By using algebra.

Anywhere from $2k-$3k

It represents an algebraic equation in the variable, k.

-47 + 6k = 3k - 2Add 47 to each side:6k = 3k +45Subtract 3k from each side:3k = 45Divide each side by 3:k = 15

1k=1ooo 2k=2ooo 3k=3000 .......and so on.......

There is no specific property to the equation.

3k-5=7k+73k-7k=7+5-4k=12k=-3